Survival analysis and prognostic factors of time to first domestic violence after marriage among Nigeria, Kenya, and Mozambique women (2020)
Objectives: How soon an ever-married woman falls a victim of domestic violence after marriage is not documented in Africa. This study sought to assess the timing of first domestic violence (FDV) against women after marriage and determined the factors associated with the timings in Nigeria, Kenya, and Mozambique. Study design: This is a cross-sectional study. Methods: Data of 29,793 ever-married women of reproductive age consisting of 21,564, 4237 and 3992 from Demographic and Health Survey conducted in Nigeria (2013), Kenya (2014) and Mozambique (2011), respectively, were used. The timing of FDV was the time interval between marriage date and date of the FDV for those with reported violence but censored as the time interval between marriage date and the survey date for those without domestic violence. Survival analysis techniques were used to assess the timing and the factors influencing the timing at (P ¼ 0.05). Results: The lifetime prevalence of domestic violence among the ever-married women in Nigeria, Kenya and Mozambique was 15.4%, 39.0% and 31.0%, respectively. The overall median time to FDV was 3 years. The risk of FDV was twice higher in Kenya (adjusted hazard ratio (aHR) ¼ 1.934; 95% confidence interval (CI): 1.729e2.132) and 15% higher in Mozambique (aHR ¼ 1.156; 95% CI: 1.156e1.223) than in Nigeria. The hazard of domestic violence was significantly higher among separated/divorced women across the three countries (aHR ¼ 1.326; 95% CI: 1.237e1.801). Other factors associated with the timing of FDV against women were respondents' education, age at first marriage, region and location of residence, religion, ethnicity, employment status, wealth quintile, spouse consuming alcohol and husbands' educational attainment. Conclusions: Domestic violence against married women by their intimate partners is prevalent across Mozambique, Nigeria and Kenya, with earlier occurrences in Kenya and Mozambique. Age at first marriage, education factors, religion, ethnicity and region of residence in each country affected the timing of the first incidence of domestic violence.